Respuestas

2012-10-10T06:14:31+02:00

-3(p + q = 3 )   = -3p -3q =-9

3p +2q = 19          3p +2q = 19

                           --------------------

                                  -1*(-q = 10 )

                                    q = -10

 p+q = 3           

 p +(-10)=3

 p -10 = 3

 p = 10+3 

 p = 13

prueba  : p + q = 3         prueba 3p +2q = 19

              13-10 = 3                   3(13)+2(-10)= 19

                    3  = 3                         39  +(-20)= 19

                                                                19 = 19